(3-Oxo-3H-benzo[f]chromen-1-yl)methyl piperidine-1-carbodithioate - Kotresh, O. (International Union of Crystallography, 2012)
In the title compound, C(20)H(19)N O(2)S(2),the 3Hbenzo-chromene ring system is nearly planar, with a maximum deviation of 0.036 (2) Å, and the piperidine ring adopts a chair conformation: the bond-angle sum for its N atom is 358.7°. The dihedral angle between the 3H-benzo[f]chromene ring and the piperidine ring is 89.07 (8)°. In the crystal, C—H⋯O hydrogen bonds lead to [010] C(6) chains and weak aromatic π–π interactions between the fused pyran ring and fused benzene ring of benzochromene [centroid–centroid distance = 3.652 (1) Å] are also observed.